Fuel cell membrane electrode frame integrated glue injection structure and method
Through the integrated glue injection structure and preparation method of membrane electrodes, the complex problem of fuel cell sealant line molding is solved, more efficient assembly and more stable sealing are achieved, and damage risk and maintenance costs are reduced.
Patent Information
- Application Number
- CN202411670198.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-01-07
AI Technical Summary
The existing fuel cell sealant line forming method is complex in operation, low assembly efficiency, and easy to damage the membrane electrodes and bipolar plates, resulting in poor sealing, increasing the maintenance cost and safety risks of fuel cells.
The film electrode integrated glue injection structure and preparation method are adopted. The frame material is cut through the knife mold and the laser machine, hot pressing and glue dispensing, and the glue injection molding is carried out in combination with the mold applying pressure to form a sealing ring to ensure the uniformity between the frame and carbon paper. seal.
It improves the stability and assembly efficiency of fuel cells, reduces the plate dispensing process, reduces the risk of membrane electrode damage, and improves the airtightness and service life.
Smart Images

Figure CN119275306A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of proton exchange membrane fuel cells, and in particular relates to a fuel cell membrane electrode integrated glue injection structure and a preparation method. Background Art
[0002] Fuel cells are online power generation devices that convert chemical energy into electrical energy. As they break through the efficiency limitations of traditional internal combustion engines, fuel cell engines are considered to be the most important direction of development for future automotive power devices. Taking proton exchange membrane fuel cells (PEMFC) as an example, the fuel cell stack is composed of multiple single cells stacked together. The gas source enters each single cell through the fuel inlet of the stack, passes through the specified sealed flow channel in the cell and participates in the reaction, and the remaining gas flows out of the stack from the outlet of the stack. To ensure the normal operation of the battery stack, the sealing of the battery stack is very critical. Poor sealing or sealing failure of the battery stack will lead to reduced performance of the battery stack, damage to the internal components of the battery stack, and even cause explosions, resulting in safety accidents. In hydrogen fuel cells, sealant lines or screen printing are usually used to seal the three-chamber fluid; among them, the screen printing process is only suitable for the internal bonding of graphite bipolar plates and the sealing of cooling channels, while the seal between the reactant gas and the membrane electrode is generally sealed with sealant lines.
[0003] At present, in the actual assembly application of fuel cell stacks, there are many ways to form the sealant line, such as using UV glue to solidify in the bipolar plate glue line groove, customizing the glue line by mold forming, injection molding or glue injection molding on the bipolar plate, and silicone molding on the membrane electrode frame. However, these sealant line forming methods require multiple dispensing or rubber ring pasting, which is not convenient for the assembly of the battery stack, has low assembly efficiency, and is easy to cause damage to core components such as the membrane electrode or bipolar plate, affecting the performance of the entire battery stack; moreover, when the fuel cell is poorly sealed due to the sealant line problem, the bipolar plate or membrane electrode needs to be replaced as a whole, which is complicated and costly, and is not conducive to the optimization and upgrading of the fuel cell. The anode plate, cathode plate and MEA of traditional PEMFC are all manufactured independently. In order to reduce the number of parts, the seal can be attached to the plate or MEA to form a combination, and then combined into a single cell by assembly pressure. Traditional single cells generally use sealing rings to seal hydrogen, air and coolant, which is called a line seal structure. Its structure is simple, intuitive and easy to process. However, due to the manufacturing errors of single-piece seals, the force stability and consistency between the plates are poor in long-term service. When the force between the surfaces is uneven, it is easy to cause a large difference in the contact electrical and thermal resistance between the inside and the nodes of the single cell, making it difficult to ensure the consistency of the whole stack during power generation. Toyota Motor Corporation has disclosed a fuel cell single cell, which basically solves the above-mentioned sealing-related problems. It does not use a O-type sealing ring to seal the bipolar plate and MEA, but uses a resin frame to limit the bipolar plate and membrane electrode. However, this structure does not make the resin frame evenly wrapped around the electrolyte membrane. Therefore, under working conditions with large temperature differences, the local pressure caused by the resin frame may damage the electrolyte membrane. Summary of the invention
[0004] The main purpose of the present invention is to propose a fuel cell membrane electrode integrated injection structure and preparation method. In order to solve the problem that the existing sealant line molding method is complicated to operate, and to improve the stability of the fuel cell and reduce the risk of damage to each component, a fuel cell membrane electrode integrated injection structure and preparation method are designed, the membrane electrode is combined into a component by injection molding, and its processing method is preliminarily explored. This structure can be used for fuel cell membrane electrode integrated injection.
[0005] To achieve the above purpose, the present invention proposes the following structure and preparation scheme The present application proposes a fuel cell membrane electrode frame integrated glue injection structure and preparation method, a membrane electrode frame integrated seal, including a membrane electrode preparation method and a frame integrated glue injection preparation method; Step 1: Cut the frame material with a die cutter and laser machine; Step 2: Lay the cut frame between the upper and lower parts of the proton exchange membrane; Step 3: After hot pressing the bonded membrane electrode, take out the membrane electrode and place it on the dispensing platform for vacuum adsorption; Step 4: After applying glue to the cathode surface of the membrane electrode, take out the carbon paper for lamination; Step 5: Place the carbon paper on the dispensing platform and vacuum adsorb to start the dispensing program to perform dispensing and perform membrane electrode anode bonding; Step 6: hot pressing the membrane electrode with carbon paper attached to obtain a prepared membrane electrode; Step 7: Press Figure 3As shown, the prepared seven-layer membrane electrode is placed on the upper mold fixture boss and adsorbed at a vacuum of 80-95Kpa, and the frame is located on the middle sealing ring of the mold, with 1-3mm of the frame exposed; Step 8: Stack the lower mold with the upper mold and the membrane electrode, apply a pressure of 0.38-0.42Ppa to the mold, so that the sealing ring is compressed to a certain extent, the lower mold contacts the boss of the upper mold and is pressed tightly, the relative positions of the upper mold, the lower mold and the membrane electrode do not change, and the positioning and fitting screws are fixed, and the parallelism between the molds is ensured to meet the design requirements. The screw fixing torque is 10-20N to fix the mold without misalignment and leakage; Step 9: Connect the glue injection inlet to the glue injection pipe, start the glue injection equipment to perform glue injection, and perform vacuum injection to avoid bubbles and uneven thickness in the sealing frame; Step 10: Adjust the heating temperature to 80-120℃, preferably 90℃, and the curing time to 3-10min, preferably 5min. During the curing process, the lower mold fixture is humidified by 50%±10% to prevent the membrane electrode from expanding. After the sealant is cured and formed, it is cooled, the mold screw is removed, and the membrane electrode is taken out.
[0006] Furthermore, in step 1, the frame material includes: one or more of polyethylene naphthalate PEN, polyimide PI, polyphenylene sulfide PPS or polyethylene terephthalate PET; the cutting is: cutting into a first layer frame film with a width of 2-5mm, a second layer frame film with a width of 2-5mm, and a frame thickness of 30-40um.
[0007] Furthermore, in step 2, the thickness of the double-frame bonding after bonding is 60-90 um.
[0008] Furthermore, in step 3, the membrane electrode frame lamination hot pressing temperature is 90°C-120°C, preferably 90°C, the membrane electrode frame hot pressing pressure is 500N-1500N, preferably 1200N, and the hot pressing time is 60-120s, preferably 90s.
[0009] Furthermore, in step 4, the glue height of the glue dispensing is 0.03-0.1 mm, preferably 0.05 mm; the glue width is 0.8-1.5 mm, preferably 1.2 mm; and the speed is 35-45 s, preferably 42 s.
[0010] Furthermore, in step 5, the carbon paper bonding glue width is 0.8mm-1.5mm, preferably 1mm; the glue height is 0.03mm-0.1mm, preferably 0.05mm; the glue dispensing speed is 35-45s; the carbon paper sealing bonding glue is one or more of hot melt glue, room temperature curing glue, UV glue or hot melt glue.
[0011] Furthermore, in step 6, the thickness of the membrane electrode reaction zone is 0.3 mm-0.8 mm; the membrane electrode hot pressing pressure is 500 N-1200 N; the hot pressing temperature is 60° C.-100° C., and the hot pressing time is 50-80 s. Furthermore, in step 3, the membrane electrode is placed on a dispensing platform with a vacuum adsorption force of 50-100 kPa.
[0012] Furthermore, in step 8, the fixing torque of the screw of the membrane electrode mold is 10N.
[0013] Furthermore, in step 9, the glue used for membrane electrode injection is liquid silicone.
[0014] Furthermore, in step 10, the curing temperature of the membrane electrode glue injection is 90° C. and the curing time is 5 minutes.
[0015] Further, the membrane electrode is tested, and the testing steps include: Step 1: Remove the mold screw, take out the membrane electrode, and test the total length of the membrane electrode frame. The total length of the membrane electrode tested by the vernier caliper is: 300-480mm; the total width is: 100-200mm; Step 2: The profilometer scans and measures the thickness of the membrane electrode frame glue to be 0.3-0.8mm, the thickness of the sealant on the frame to be 0.5-1.2mm, and the sealing width to be 1.6-2.5mm; Step 3: Place the membrane electrode into the airtight test fixture, inflate with 50KPa, test for 1 minute, and the leakage is 0.1-0.25sccm; Step 4: The prepared membrane electrode is subjected to a ten-piece short stack assembly and a three-cavity leakage test. The short stack assembly cylinder pressure is 0.38-0.4Mpa, and the three pipes for the air tightness test are connected, namely, the hydrogen / oxygen / water three-cavity, the inflation time is 30s, the air pressure is 200kpa, the test time is 1min, and the test value is 4-10sccm to meet the air tightness test conditions; Step 5: Activate and polarize the short stack. The short stack performance test result is 0.6-0.65 / @1.6-1.8A / cm 2 .
[0016] Furthermore, the thickness of the membrane electrode glue injection frame is 0.34-0.5 mm, preferably 0.34 mm; The thickness of the sealant is 0.5-0.7 mm, preferably 0.60 mm, and the sealing width is 1.85-2.2 mm, preferably 2 mm; the total length of the membrane electrode frame is 456 mm ± 0.1 mm; the total width is 120 mm ± 0.1 mm.
[0017] Furthermore, the three-cavity external leakage value of the membrane electrode gas tightness test is <0.5sccm / piece@200Kpa, and the hydrogen-air internal leakage of the membrane electrode gas tightness test is <0.25sccm / piece@50Kpa.
[0018] Compared with the prior art, the advantages of the present invention are as follows: (1) The present invention optimizes the structure to adapt to injection molding based on the membrane electrode frame with an active area of 400 cm.
[0019] (2) The integrated glue injection structure of the fuel cell membrane electrode frame of the present invention can protect the membrane electrode, so a gap of 1 mm is left between the frame and the carbon paper so that the sealant can wrap the frame and penetrate into the edge of the carbon paper.
[0020] (3) The integrated glue injection structure of the fuel cell membrane electrode frame of the present invention can make the plate bear force evenly and seal well. Compared with the glue point structure, the glue point process of the plate is reduced. The integrated glue injection process of the membrane electrode frame is conducive to batch processing and manufacturing, and improves the assembly efficiency and yield rate of the fuel cell stack.
[0021] (4) The integrated glue injection structure of the fuel cell membrane electrode frame of the present invention can prevent the membrane electrode frame from being dislocated and deformed, which is conducive to the neat assembly of the fuel cell stack.
[0022] (5) The integrated glue injection structure of the fuel cell membrane electrode frame of the present invention can reduce the risk of membrane electrode tearing and improve the airtightness qualification rate and other service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is the structure diagram of membrane electrode injection molding; Figure 2 It is a performance test diagram of membrane electrode integrated injection molding, wherein a, b, and c represent Example 1, Example 2, and Example 3 respectively.
[0024] Figure 3 Diagram of the membrane electrode assembly structure.
[0025] Figure 1 The various components are as follows: air inlet 1, water inlet 2, hydrogen outlet 3, double-sided sealing tape 4, air outlet 5, water outlet 6, hydrogen inlet 7, membrane electrode carbon paper 8, and glue injection molding frame 9.
[0026] Figure 3 The various components are as follows: A1 lower mold, A2 vacuum port, A3 upper mold, A4 vacuum platform, A5 injection port, A6 membrane electrode placement area, A7 humidity port. DETAILED DESCRIPTION
[0027] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] In the following embodiments, the membrane electrode assembly structure is shown in FIG. Figure 3 As shown, it includes a lower mold A1, a vacuum port A2, an upper mold A3, a vacuum platform A4, a glue injection port A5, a membrane electrode placement area A6 and a humidity port A7; the lower mold A1 and the upper mold A3 are fixed by screws, and a vacuum platform A4 is formed inside after bonding, the lower mold A1 is provided with a membrane electrode placement area A6, the upper mold A3 is provided with a glue injection port A5, and the glue injection port A5 is connected to the vacuum platform A4, and the side of the lower mold A1 is provided with a vacuum port A2 and a humidity port A7.
[0029] Example 1 Step 1: Use polyethylene terephthalate (PET) film electrode frame material for die cutting and laser cutting, cutting into a first layer frame film width of 3mm, a second layer frame film width of 3mm, and a frame thickness of 38um.
[0030] Step 2: Lay the cut frame between the upper and lower parts of the proton exchange membrane. The thickness of the double frame is 76um.
[0031] Step 3: Hot press the bonded membrane electrode and frame at a temperature of 90°C, a time of 80 seconds, and a pressure of 1200N. Take out the membrane electrode and place it on a dispensing platform for vacuum adsorption.
[0032] Step 4: Apply glue to the cathode surface of the membrane electrode with a glue height of 0.05 mm, a glue width of 1.2 mm, and a speed of 42 s. Take out the carbon paper for bonding.
[0033] Step 5: Place the carbon paper on the dispensing platform and start the dispensing program for vacuum adsorption. The glue height is 0.05mm, the glue width is 1.0mm, and the speed is 42s to perform membrane electrode anode bonding.
[0034] Step 6: hot-press the bonded membrane electrode at a temperature of 100°C, a press pressure of 1000N, and a hot-pressing time of 60s to obtain a prepared membrane electrode.
[0035] Step 7: Press Figure 3 As shown, the prepared membrane electrode is placed on the upper mold fixture boss and adsorbed at a vacuum of 93Kpa. The frame is located on the middle sealing ring of the mold, with 1mm of the frame exposed.
[0036] Step 8: Stack the lower mold with the upper mold and the membrane electrode, apply 0.4Ppa pressure to the mold to compress the sealing ring to a certain extent, the lower mold contacts the boss of the upper mold and is pressed tightly, the relative positions of the upper mold, lower mold and membrane electrode do not change, and fix them with positioning screws, and ensure that the parallelism between the molds meets the design requirements. The screw fixing torque of 15N fixes the mold to prevent misalignment and leakage.
[0037] Step 9: Connect the glue injection inlet to the glue injection pipe, start the glue injection equipment to perform glue injection, and perform vacuum injection to avoid bubbles and uneven thickness in the sealing frame.
[0038] Step 10: Adjust the heating temperature to 80℃ and the curing time to 5 minutes. During the curing process, humidify the lower mold fixture by 50%±10% to avoid expansion of the membrane electrode. After the sealant is cured and formed, cool it for 3 minutes.
[0039] Step 11: Remove the mold screw, take out the membrane electrode, and test the total length of the membrane electrode frame. The vernier caliper test shows that the total length of the membrane electrode is 455.9 mm and the total width is 119.9 mm.
[0040] Step 12: The profilometer scans and measures the thickness of the membrane electrode frame glue to be 0.34mm, the thickness of the sealant on the frame to be 0.55mm, and the sealing width to be 1.9mm.
[0041] Step 13: Place the membrane electrode into the airtight test fixture, inflate with 50KPa for 1 minute, and the leakage is 0.225sccm.
[0042] Step 14: The prepared membrane electrode was subjected to ten-piece short stack assembly and three-cavity leakage test. The short stack assembly cylinder pressure was 0.4Mpa, and the three pipes connected for airtightness test were hydrogen / oxygen / water chambers. The inflation time was 30s, the air pressure was 200kpa, the test time was 1min, and the test value was 5.0sccm. The airtightness test value was too large.
[0043] Step 15: Activate and polarize the short stack. The short stack performance test result is 0.608 / @1.8A / cm 2 .
[0044] The structure diagram of membrane electrode injection molding in this embodiment is as follows Figure 1 As shown, it includes: an air inlet 1, a water inlet 2, a hydrogen outlet 3, a double-sided sealing tape 4, an air outlet 5, a water outlet 6, a hydrogen inlet 7, a membrane electrode carbon paper 8, and a glue injection forming frame; the air inlet 1, the water inlet 2, the hydrogen outlet 3 and the air outlet 5, the water outlet 6, the hydrogen inlet 7 are respectively arranged on both sides of the membrane electrode plate, and are covered with a double-sided sealing tape 4 on top, a membrane electrode carbon paper 8 is arranged at the center of the membrane electrode, and the frame of the membrane electrode is a glue injection forming frame 9.
[0045] Example 2 Step 1: Cut the polyimide (PI) film electrode frame material with a die cutter and a laser machine, and cut it into a first layer frame film with a width of 3mm, a second layer frame film with a width of 3mm, and a frame thickness of 40um.
[0046] Step 2: Lay the cut frame between the upper and lower parts of the proton exchange membrane. The thickness of the double frame is 80um.
[0047] Step 3: Hot press the bonded membrane electrode and frame at a temperature of 100°C, a time of 80 seconds, and a pressure of 1200N. Take out the membrane electrode and place it on a dispensing platform for vacuum adsorption.
[0048] Step 4: Apply glue to the cathode surface of the membrane electrode with a glue height of 0.05 mm, a glue width of 1.2 mm, and a speed of 42 s. Take out the carbon paper for bonding.
[0049] Step 5: Place the carbon paper on the dispensing platform and start the dispensing program for vacuum adsorption. The glue height is 0.05mm, the glue width is 1.0mm, and the speed is 42s to perform membrane electrode anode bonding.
[0050] Step 6: hot-press the bonded membrane electrode at a temperature of 100°C, a press pressure of 1000N, and a hot-pressing time of 80s to obtain the prepared membrane electrode.
[0051] Step 7: Press Figure 3 As shown, the prepared membrane electrode is placed on the upper mold fixture boss and adsorbed at a vacuum of 93Kpa. The frame is located on the middle sealing ring of the mold, with 1mm of the frame exposed.
[0052] Step 8: Stack the lower mold with the upper mold and the membrane electrode, apply 0.4Ppa pressure to the mold to compress the sealing ring to a certain extent, the lower mold contacts the boss of the upper mold and is pressed tightly, the relative positions of the upper mold, lower mold and membrane electrode do not change, and fix them with positioning screws, and ensure that the parallelism between the molds meets the design requirements. The screw fixing torque of 15N fixes the mold to prevent misalignment and leakage.
[0053] Step 9: Connect the glue injection inlet to the glue injection pipe, start the glue injection equipment to perform glue injection, and perform vacuum injection to avoid bubbles and uneven thickness in the sealing frame.
[0054] Step 10: Adjust the heating temperature to 100℃ and the curing time to 5 minutes. During the curing process, the lower mold fixture is humidified by 50%±10% to prevent the membrane electrode from expanding. After the sealant is cured and formed, cool it for 3 minutes.
[0055] Step 11: Remove the mold screw, take out the membrane electrode, and test the total length of the membrane electrode frame. The vernier caliper test shows that the total length of the membrane electrode is 456.1 mm and the total width is 120.1 mm.
[0056] Step 12: The profilometer scans and measures the thickness of the membrane electrode frame glue to be 0.34mmm, the thickness of the sealant on the frame to be 0.238mm, and the sealing width to be 2.1mm.
[0057] Step 13: Place the membrane electrode into the airtight test fixture, inflate with 50KPa, test for 1 minute, and the leakage is 0.23sccm.
[0058] Step 14: Assemble the prepared membrane electrode into ten short stacks and conduct a three-cavity leakage test. The short stack assembly cylinder pressure is 0.4Mpa, and the three pipes connected for airtightness test are hydrogen / oxygen / water chambers. The inflation time is 30s and the air pressure is 200kpa. The test time is 1min and the test value is 4.9sccm, which meets the airtightness test conditions.
[0059] Step 15: The short stack is activated and polarized for performance testing. The short stack performance test result is 0.630 / @1.8A / cm 2 .
[0060] Example 3 Step 1: Cut the polyphenylene sulfide (PPS) membrane electrode frame material with a die cutter and a laser machine, and cut it into a first layer frame film with a width of 3mm, a second layer frame film with a width of 3mm, and a frame thickness of 40um.
[0061] Step 2: Lay the cut frame between the upper and lower parts of the proton exchange membrane. The thickness of the double frame is 80um.
[0062] Step 3: Hot press the bonded membrane electrode and frame at a temperature of 120°C, a time of 80 seconds, and a pressure of 1200N. Take out the membrane electrode and place it on a dispensing platform for vacuum adsorption.
[0063] Step 4: Apply glue to the cathode surface of the membrane electrode with a glue height of 0.05 mm, a glue width of 1.2 mm, and a speed of 42 s. Take out the carbon paper for bonding.
[0064] Step 5: Place the carbon paper on the dispensing platform and start the dispensing program for vacuum adsorption. The glue height is 0.05mm, the glue width is 1.0mm, and the speed is 42s to perform membrane electrode anode bonding.
[0065] Step 6: hot-press the bonded membrane electrode at a temperature of 100°C, a press pressure of 1000N, and a hot-pressing time of 80s to obtain the prepared membrane electrode.
[0066] Step 7: Press Figure 3 As shown, the prepared membrane electrode is placed on the upper mold fixture boss and adsorbed at a vacuum of 93Kpa. The frame is located on the middle sealing ring of the mold, with 1mm of the frame exposed.
[0067] Step 8: Stack the lower mold with the upper mold and the membrane electrode, apply 0.4Ppa pressure to the mold to compress the sealing ring to a certain extent, the lower mold contacts the boss of the upper mold and is pressed tightly, the relative positions of the upper mold, lower mold and membrane electrode do not change, and fix them with positioning screws, and ensure that the parallelism between the molds meets the design requirements. The screw fixing torque of 15N fixes the mold to prevent misalignment and leakage.
[0068] Step 9: Connect the glue injection inlet to the glue injection pipe, start the glue injection equipment to perform glue injection, and perform vacuum injection to avoid bubbles and uneven thickness in the sealing frame.
[0069] Step 10: Adjust the heating temperature to 90℃ and the curing time to 5 minutes. During the curing process, the lower mold fixture is humidified by 50%±10% to prevent the membrane electrode from expanding. After the sealant is cured and formed, cool it for 3 minutes.
[0070] Step 11: Remove the mold screw, take out the membrane electrode, and test the total length of the membrane electrode frame. The vernier caliper test shows that the total length of the membrane electrode is 340 mm and the total width is 108 mm.
[0071] Step 12: The profilometer scans and measures the thickness of the membrane electrode frame glue to be 0.34mmm, the thickness of the sealant on the frame to be 0.8mm, and the sealing width to be 2mm.
[0072] Step 13: Place the membrane electrode into the airtight test fixture, inflate with 50KPa and test for 1 minute. The leakage is 0.189sccm.
[0073] Step 14: Assemble the prepared membrane electrode into ten short stacks and conduct a three-cavity leakage test. The short stack assembly cylinder pressure is 0.4Mpa, and the three pipes connected for airtightness test are hydrogen / oxygen / water chambers. The inflation time is 30s and the air pressure is 200kpa. The test time is 1min, and the test value is 4.5sccm, which meets the airtightness test conditions.
[0074] Step 15: The short stack is activated and polarized for performance testing. The performance test result of the short stack is 0.648 / @1.8A / cm 2 .
[0075] The embodiments of the present invention are described above in conjunction with the accompanying drawings, but the present invention is not limited to the above-mentioned specific implementation modes, which are merely illustrative rather than restrictive. Under the guidance of the present invention, ordinary technicians in this field can also make many forms without departing from the scope of protection of the present invention and the claims, all of which are within the protection of the present invention.
Claims
1. A fuel cell membrane electrode frame integrated glue injection method, characterized in that: Membrane electrode frame integrated sealing, including a membrane electrode preparation method and a frame integrated glue injection preparation method; Step 1: Cut the frame material with a die cutter and laser machine; Step 2: Lay the cut frame between the upper and lower parts of the proton exchange membrane; Step 3: After hot pressing the bonded membrane electrode, take out the membrane electrode and place it on the dispensing platform for vacuum adsorption; Step 4: After applying glue to the cathode surface of the membrane electrode, take out the carbon paper for lamination; Step 5: Place the carbon paper on the dispensing platform and vacuum adsorb to start the dispensing program to perform dispensing and perform membrane electrode anode bonding; Step 6: hot pressing the membrane electrode bonded with carbon paper to obtain a prepared membrane electrode; Step 7: Place the prepared seven-layer membrane electrode on the upper mold fixture boss under vacuum of 80-95Kpa for adsorption, with the frame located on the middle sealing ring of the mold, exposing 1-3mm of the frame; Step 8: Stack the lower mold with the upper mold and the membrane electrode, apply a pressure of 0.38-0.42Ppa to the mold, so that the sealing ring is compressed to a certain extent, the lower mold contacts the boss of the upper mold and is pressed tightly, the relative positions of the upper mold, the lower mold and the membrane electrode do not change, and the positioning and fitting screws are fixed, and the parallelism between the molds is ensured to meet the design requirements. The screw fixing torque is 10-20N to fix the mold without misalignment and leakage; Step 9: Connect the glue injection inlet to the glue injection pipe, start the glue injection equipment to perform glue injection, and perform vacuum injection to avoid bubbles and uneven thickness in the sealing frame; Step 10: Adjust the heating temperature to 80-120℃ and the curing time to 3-10min. During the curing process, humidify the lower mold fixture by 50%±10% to prevent the membrane electrode from expanding. After the sealant is cured and formed, cool it, remove the mold screw, and take out the membrane electrode.
2. A fuel cell membrane electrode frame integrated glue injection structure and preparation method according to claim 1, characterized in that: In step 1, the frame material includes: one or more of polyethylene naphthalate PEN, polyimide PI, polyphenylene sulfide PPS or polyethylene terephthalate PET; the cutting is: cutting into a first layer frame film width of 2-5mm, a second layer frame film width of 2-5mm, and a frame thickness of 30-40um; In step 2, the thickness of the double-frame bonding after bonding is 60-90um; In step 3, the membrane electrode frame bonding hot pressing temperature is 90°C-120°C, the membrane electrode frame hot pressing pressure is 500N-1500N, and the hot pressing time is 60-120s; In step 4, the glue height of the glue dispensing is 0.03-0.1mm; the glue width is 0.8-1.5mm; and the speed is 35-45s; In step 5, the carbon paper bonding glue width is 0.8mm-1.5mm; the glue height is 0.03mm-0.1mm; the dispensing speed is 35-45s; the carbon paper sealing bonding glue is one or more of hot melt glue, room temperature curing glue, UV glue or hot melt glue; In step 6, the thickness of the membrane electrode reaction zone is 0.3 mm-0.8 mm; the membrane electrode hot pressing pressure is 500 N-1200 N; the hot pressing temperature is 60° C.-100° C., and the hot pressing time is 50-80 s.
3. According to claim 1, the fuel cell membrane electrode frame integrated glue injection structure and preparation method is characterized in that: In step 3, the membrane electrode is placed on a dispensing platform with a vacuum adsorption force of 50-100 kPa.
4. According to claim 1, the fuel cell membrane electrode frame integrated glue injection structure and preparation method is characterized in that: In step 8, the fixing torque of the screw of the membrane electrode mold is 10N.
5. According to claim 1, the fuel cell membrane electrode frame integrated glue injection structure and preparation method is characterized in that: In step 9, the glue used for membrane electrode injection is liquid silicone.
6. The fuel cell membrane electrode frame integrated glue injection structure and preparation method according to claim 1, characterized in that: In step 10, the curing temperature of the membrane electrode glue injection is 90° C. and the curing time is 5 minutes.
7. The fuel cell membrane electrode frame integrated glue injection structure and preparation method according to claim 1, characterized in that: The membrane electrode is tested, and the test steps include: Step 1: Remove the mold screw, take out the membrane electrode, and test the total length of the membrane electrode frame. The total length of the membrane electrode tested by the vernier caliper is: 300-480mm; the total width is: 100-200mm; Step 2: The profilometer scans and measures the thickness of the membrane electrode frame glue to be 0.3-0.8mm, the thickness of the sealant on the frame to be 0.5-1.2mm, and the sealing width to be: 1.6-2.5mm; Step 3: Place the membrane electrode into the airtight test fixture, inflate with 50KPa, test for 1 minute, and the leakage is 0.1-0.25sccm; Step 4: The prepared membrane electrode is subjected to a short stack assembly of ten pieces and a three-chamber leakage test. The short stack assembly cylinder pressure is 0.38-0.4Mpa, and the three pipes for the air tightness test are connected, namely, the hydrogen / oxygen / water three chambers. The filling time is 30s, the air pressure is 200kpa, the test time is 1min, and the test value is 4-10sccm to meet the air tightness test conditions; Step 5: Activate and polarize the short stack. The short stack performance test result is 0.6-0.65 / @1.6-1.8A / cm 2 .
8. The fuel cell membrane electrode frame integrated glue injection structure and preparation method according to claim 1, characterized in that: The thickness of the membrane electrode glue injection frame is 0.34-0.5mm; The thickness of the sealant is 0.5-0.7 mm, and the sealing width is 1.85-2.2 mm.
9. The fuel cell membrane electrode frame integrated glue injection structure and preparation method according to claim 1, characterized in that: The total length of the membrane electrode frame is 456 mm ± 0.1 mm; the total width is 120 mm ± 0.1 mm.
10. The fuel cell membrane electrode frame integrated glue injection structure and preparation method according to claim 1, characterized in that: The three-cavity external leakage value of the membrane electrode air tightness test is <0.5sccm / piece@200Kpa, and the hydrogen-air internal leakage of the membrane electrode gas tightness test is <0.25sccm / piece@50Kpa.
Citation Information
Patent Citations
Fuel cell membrane electrode sealing device and preparation method thereof
CN111129539A
Activation method and system of hydrogen fuel cell stack
CN116314947A
Offline test method for mass production of galvanic piles
CN117712427A